PENGARUH TAX RISK, GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP TAX AVOIDANCE - Anggraini Firsana Wayne; Fidiana Fidiana (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This research examines the effect of Tax Risk, audit committee, independent commissioner board, and leverage on tax avoidance at State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Furthermore, the research applies a quantitative approach. The data were taken from the companies’ annual reports and financial statements listed on the IDX. The data were collected using purposive sampling, with 15 companies as samples and a total of 60 observations during the four-year period. The data were analyzed using multiple linear regression after fulfilling the classical assumption tests. The results of testing and analysis show that Tax Risk has a positive effect on tax avoidance at State-Owned Enterprises (BUMN). However, the audit committee has a negative effect on tax avoidance, while the independent commissioner board does not affect tax avoidance. Meanwhile, leverage has a positive effect on tax avoidance. These findings indicate that corporate governance mechanisms and capital structure have different roles in influencing tax avoidance practices in State-Owned Enterprises (BUMN).